2021
DOI: 10.1002/joc.7084
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of the diurnal cycle in the variability of rainfall

Abstract: In order to quantify how much variability is affected by the diurnal cycle (DC), two variance‐partitioning schemes were applied on two rainfall datasets that cover the Intra Americas Seas (IAS) domain at a 3‐hourly resolution during 21 years. The datasets are the Tropical Rainfall Measurement Mission (TRMM) 3B42, and a simulation from the Centre National de Recherches Météorologiques (CNRM) model. From TRMM, the results show that the variance attributable to the DC is large because it shapes the variability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…The time series shows that all data sets capture an inverse dry (wet) SPI and SPEI response induced by the teleconnection signals over the NAM (MSD) based on correlations, in agreement with previous observational studies (Cavazos et al, 2020; Méndez & Magaña, 2010; Seager et al, 2009; Vega‐Camarena et al, 2018, 2023; Zermeño‐Díaz & Mendoza, 2023). Drought occurrence in the NAM is strongly related to La Niña (negative Niño 1+2) during the positive AMO, while droughts in the MSD region tend to occur during El Niño (positive ONI) of the positive PDO phase, indistinctive of the AMO phase.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The time series shows that all data sets capture an inverse dry (wet) SPI and SPEI response induced by the teleconnection signals over the NAM (MSD) based on correlations, in agreement with previous observational studies (Cavazos et al, 2020; Méndez & Magaña, 2010; Seager et al, 2009; Vega‐Camarena et al, 2018, 2023; Zermeño‐Díaz & Mendoza, 2023). Drought occurrence in the NAM is strongly related to La Niña (negative Niño 1+2) during the positive AMO, while droughts in the MSD region tend to occur during El Niño (positive ONI) of the positive PDO phase, indistinctive of the AMO phase.…”
Section: Discussionsupporting
confidence: 88%
“…Droughts or precipitation deficit over the CAM domain have been partially attributed to individual or combined phases of different teleconnections, such as El Niño‐Southern Oscillation (ENSO), the Pacific Multidecadal Oscillation (PDO) and the Atlantic Multidecadal Oscillation (AMO) (e.g., Abiy et al, 2019; Aryal & Zhu, 2021; Cavazos et al, 2020; Gershunov & Barnett, 1998; Hidalgo et al, 2015; McCabe et al, 2004; McCrary & Randall, 2010; Méndez & Magaña, 2010; Seager et al, 2009; Vega‐Camarena et al, 2018, 2023; Zermeño‐Díaz & Mendoza, 2023). For example, drier years over the southwest United States and northwest Mexico, and wetter years in the MSD, have been linked to negative ENSO (La Niña) phases (Cook et al, 2007; Hoerling & Kumar, 2003; Méndez & Magaña, 2010; Seager et al, 2009; Vega‐Camarena et al, 2023; Zermeño‐Díaz & Mendoza, 2023), and the positive AMO (Abiy et al, 2019; Aryal & Zhu, 2021; Cavazos et al, 2020; Méndez & Magaña, 2010). Méndez and Magaña (2010) also observed that during the negative PDO, there is a weakening of the Caribbean low‐level jet and an increase in easterly waves that could be related to droughts (wet period) in northern Mexico (MSD) due to increased tropical convection, which induces less northward moisture influx and subsidence west of the convection region.…”
Section: Introductionmentioning
confidence: 99%